Digital Educational Resources in the Teaching and Learning of Natural Sciences - Becerra-Brito, Cecilia (2025)
Introduction. The growing digitalization of education makes it necessary to analyze digital resources in Natural Sciences to evaluate their effectiveness and guide teacher training. Objective and methodology. This qualitative, descriptive and retrospective study aims to analyze in depth the research conducted in the last decades on the educational resources available for the teaching and learning of natural sciences. A literature review of 33 articles indexed in Scopus and Dialnet, filtered through the PRISMA method, was carried out. Results and conclusions. The results highlight the presence of various types of digital resources in secondary education, which are associated with increased attention, motivation, and improved performance. In conclusion, it is necessary to expand pedagogical integration, diversify the thematic focus, and evaluate the actual effectiveness of these resources in learning.